Simple ?

Calculus Level 3

You just need to get the very first step

This is my original

0 π / 2 1 1 + sin x d x \int _{ 0 }^{ \pi /2 }{ \frac { 1 }{ { 1+\sin x } } } dx

Hint: Think simple(Trigonometry you had probably learnt in 9th or 10th)


The answer is 1.00.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Jack Lam
Mar 19, 2015

Solution 1: Make the substitution sin x = 2 t 1 + t 2 \sin x = \frac{2t}{1+t^{2}} where t = tan x 2 t = \tan \frac{x}{2}

Change the integration borders by substituting the values of x into t, which gives tan 0 = 0 \tan 0 = 0 and tan π 4 = 1 \tan \frac{\pi}{4} = 1

Take the derivative of t with respect to x, giving d t d x = 1 2 sec 2 x 2 \frac{dt}{dx} = \frac{1}{2}\sec^{2}\frac{x}{2}

Replacing with the identity sec 2 θ = 1 + tan 2 θ \sec ^{2} \theta = 1 + \tan ^{2} \theta we get d t d x = 1 + t 2 2 \frac{dt}{dx} = \frac{1 + t^{2}}{2}

Rearranging for dx, we get d x = 2 d t 1 + t 2 dx = \frac{2dt}{1+t^{2}}

Returning back to the given integral, and substituting sinx, dx and the integration borders, we have 0 1 1 1 + 2 t 1 + t 2 2 d t 1 + t 2 \int _{ 0 }^{ 1 }{ \frac { 1 }{ 1+\frac { 2t }{ 1+t^{2} } } } \frac { 2dt }{ 1+t^{2} }

Simplifying, we get 0 1 2 d t 1 + t 2 + 2 t \int _{ 0 }^{ 1 }{ \frac { 2dt }{ 1+t^{2}+2t } }

Note that the denominator is a perfect square. Using negative indices, we get 0 1 2 ( 1 + t ) 2 d t \int _{ 0 }^{ 1 }{ 2(1+t)^{-2}dt }

This can now be evaluated easily using the power rule, since the term being indexed is linear.

This yields 2 ( 1 + t ) 1 0 1 -2(1+t)^{ -1 }{ | }_{ 0 }^{ 1 }

Converting back into a fraction and applying the borders, we get 2 1 + 1 2 1 + 0 \frac{-2}{1+1}-\frac{-2}{1+0}

Which simplifies to 1 1

Solution 2: Make the substitution 1 + sin θ = 2 sin 2 2 θ + π 4 1+\sin \theta = 2\sin ^{2} \frac{2\theta + \pi}{4}

Let u = 2 x + π 4 , d u = d x 2 u = \frac{2x+\pi}{4}, du = \frac {dx}{2}

Using the identity 1 sin θ = csc θ \frac{1}{\sin\theta} = \csc\theta and all the substitutions above, the integral is now transformed into 0 π 2 csc 2 u d u \int _{ 0 }^{ \frac { \pi }{ 2 } }{ \csc^{2} u du }

The integral of csc 2 u d u \csc^{2} u du is cot u -\cot u

The integral is now cot u 0 π 2 - \cot u{ | }_{ 0 }^{ \frac{\pi}{2} }

Substituting u back for x and evaluating the borders, we have cot π + π 4 + cot π 4 - \cot \frac{\pi + \pi}{4} + \cot \frac{\pi}{4}

Which evaluates to 1 1

Solution 3: Multiply the numerator and denominator by 1 sin x 1- \sin x

Yielding 1 sin x 1 sin 2 x = 1 sin x cos 2 x = sec 2 x tan x sec x \frac{1- \sin x}{1-\sin^{2} x} = \frac{1- \sin x}{\cos^{2} x} = \sec^{2} x - \tan x \sec x

The integral is now 0 π 2 sec 2 x sec x tan x \int _{ 0 }^{ \frac { \pi }{ 2 } }{\sec^{2} x - \sec x \tan x }

Standard Integrals:

sec x tan x d x = sec x \int {\sec x \tan x dx} = \sec x

sec 2 x d x = tan x \int {\sec^{2} x dx} = \tan x

Resulting in: ( tan x sec x ) 0 π 2 (\tan x - \sec x) { | }_{ 0 }^{ \frac{\pi}{2} }

Because we cannot evaluate this directly, we must transform the expression into something that can be evaluated.

tan x sec x = tan 2 x sec 2 x tan x + sec x \tan x - \sec x = \frac{\tan^{2} x - \sec^{2} x}{\tan x + \sec x}

Since 1 + tan 2 x = sec 2 x 1 + \tan^2 x = \sec^2 x it follows that tan 2 x sec 2 x = 1 \tan^{2} x - \sec^{2} x = -1

tan 2 x sec 2 x tan x + sec x = 1 tan x + sec x = 1 sin x + 1 cos x = cos x 1 + sin x \frac{\tan^{2} x - \sec^{2} x}{\tan x + \sec x} = \frac{-1}{\tan x + \sec x} = \frac{-1}{\frac{\sin x +1}{\cos x}} = \frac{-\cos x}{1+ \sin x}

This form can now be evaluated. Plugging in the borders:

cos x 1 + sin x 0 π 2 = 0 1 + 1 ( 1 1 + 0 ) = 1 \frac{-\cos x}{1+ \sin x} { | }_{ 0 }^{ \frac{\pi}{2} } = \frac{0}{1+1} -(\frac{-1}{1+0}) = 1

Nice solution

Mayank Singh - 6 years, 2 months ago

Log in to reply

Haha... was looking over every step when the answer was still incorrect... At least I know I'm right now.

Jack Lam - 6 years, 2 months ago

Log in to reply

Well, it would be easier if you replace sin x by cos (π/2-x)

Mayank Singh - 6 years, 2 months ago

Log in to reply

@Mayank Singh It would have been much easier if we had multiplied numerator and denominator by (1-sinx)

Shivam Hinduja - 6 years, 2 months ago

Log in to reply

@Shivam Hinduja How would that work? All I got was undefined things.

Jack Lam - 6 years, 2 months ago

Log in to reply

@Jack Lam Oh! Sorry I just evaluated (∞ - ∞) = 0 . But, the method would evaluate the indefinite integral.

Shivam Hinduja - 6 years, 2 months ago

such a long and bad method!!! uh!!

Log in to reply

Then maybe you can post a better one? I'm sure there are faster ways, but they're not immediately obvious to me.

Jack Lam - 6 years ago

Log in to reply

my method was similar to that of shivam hinduja!! +no offence to ur post really!!

Log in to reply

@A Former Brilliant Member Would that require the use of limits or geometric analysis? Because the undefined states of the integral cannot be evaluated analytically...

Jack Lam - 5 years, 12 months ago

Log in to reply

@Jack Lam u simply had to change the sec-tan form to 1/(sec+tan) from then u would evaluate it

A Former Brilliant Member - 5 years, 12 months ago

Log in to reply

@A Former Brilliant Member Got it. Edited my solution to incorporate it as the third method.

Jack Lam - 5 years, 12 months ago

Log in to reply

@Jack Lam +1 for that

A Former Brilliant Member - 5 years, 12 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...